A visualização matemática em jogos educacionais digitais no Brasil - Cruz, Paulo Fernando Costa da [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The main objective of this research is to contribute to Mathematics Education in the study of the application of mathematical visualization in digital educational games. The specific objectives are to carry out a bibliographical research, in the form of a systematic review of the literature, to verify the existence of academic texts in Brazil, from 2019 to 2023, that report the use of digital games that apply mathematical visualization and , also, carrying out an experiment to develop a digital educational game with a strong emphasis on mathematical visualization with the qualitative evaluation of the effects of applying mathematical visualization on students through this game, carried out by educators linked to the teaching of mathematics. The problem to be studied took the form of the following research question: The application of mathematical visualization in digital educational games brings, to students, motivation, entertainment, understanding of mathematics, stimulation of logical reasoning and help in solving problems and, therefore, can it be considered effective for learning mathematics? In an attempt to find a solution to the proposed problem, preexperimental research was developed, of an applied nature, with a descriptive objective and a qualitative approach, which consisted of the development of a digital educational game and its evaluation by educators linked to the area of mathematics. The results of the experiment were not entirely convincing, as at one point the educators attributed the effects on students to mathematical visualization and at another to the game. Therefore, we suggest carrying out further and more precise research to truly verify the value of applying this Mathematics Education technique through digital educational games. Possibly, carrying out experimental research, with samples sized by statistical techniques and the use of more variables, could in the future establish a clearer panorama about the value of using mathematical visualization in digital educational games, contributing to the development of this technique.

O objetivo principal dessa pesquisa é contribuir com a Educação Matemática no estudo da aplicação da visualização matemática em jogos educacionais digitais. Os objetivos específicos são a realização de uma pesquisa bibliográfica, na forma de uma revisão sistemática da literatura, para verificar a existência de textos acadêmicos no Brasil, no período de 2019 a 2023, que relatam o uso de jogos digitais que aplicam a visualização matemática e, também, a realização de um experimento de desenvolvimento de um jogo educacional digital com forte ênfase na visualização matemática com a avaliação qualitativa dos efeitos da aplicação da visualização matemática sobre os estudantes por meio desse jogo, feita por educadores ligados ao ensino da matemática. o problema a ser estudado tomou a forma da seguinte questão de pesquisa: A aplicação da visualização matemática nos jogos educacionais digitais traz, para os estudantes, motivação, entretenimento, compreensão da matemática, estímulo do raciocínio lógico e ajuda na resolução de problemas e, portanto, pode ser considerada eficaz para a aprendizagem da matemática? Na tentativa de buscar uma solução para o problema proposto foi desenvolvida uma pesquisa pré-experimental, de natureza aplicada, com objetivo descritivo e abordagem qualitativa, que consistiu no desenvolvimento de um jogo educacional digital e sua avaliação por educadores ligados à área da matemática. Os resultados do experimento não se mostraram inteiramente convincentes, pois em determinado momento os educadores atribuíram os efeitos sobre os estudantes à visualização matemática e em outro ao jogo. Portanto, sugerimos a realização de maiores e mais precisas pesquisas para realmente verificar o valor da aplicação dessa técnica de Educação Matemática por meio dos jogos educacionais digitais. Possivelmente, a realização de pesquisas experimentais, com amostras dimensionadas por técnicas da Estatística e o uso de mais variáveis possa futuramente estabelecer um panorama mais claro sobre o valor do uso da visualização matemática em jogos educacionais digitais, contribuindo para o desenvolvimento dessa técnica.
Mathematical visualization in digital educational games in Brazil
Keywords: Visualização da informação; Ciência da computação; Matemática; Jogos em educaçação matemática; Visualization; Mathematics; Educational; Figital; Game